2015
DOI: 10.1378/chest.14-2181
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Why Patients With COPD Get Readmitted

Abstract: BACKGROUND:Th e Hospital Readmissions Reduction Program (HRRP) penalizes hospitals for 30-day readmissions and was extended to COPD in October 2014. Th ere is limited evidence available on readmission risk factors and reasons for readmission to guide hospitals in initiating programs to reduce COPD readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
82
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(93 citation statements)
references
References 23 publications
10
82
1
Order By: Relevance
“…The results of this study extend the findings of previous research reporting a strong association between post-discharge care including early follow-up with lower risk of readmission 29,3639. Sharma et al36 reported that early follow-up visits with patient’s PCP significantly reduced risk of ED visits and readmissions within 30 days following acute hospitalization.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of this study extend the findings of previous research reporting a strong association between post-discharge care including early follow-up with lower risk of readmission 29,3639. Sharma et al36 reported that early follow-up visits with patient’s PCP significantly reduced risk of ED visits and readmissions within 30 days following acute hospitalization.…”
Section: Discussionsupporting
confidence: 86%
“…Results from several observational studies showed that more than one-half of COPD exacerbations were not reported to health care providers and that these had significant impact on health status 39,40. Wilkinson et al34 found that failure to report exacerbations was associated with an increased risk of hospitalization, while earlier treatment of COPD exacerbation accelerates recovery time.…”
Section: Discussionmentioning
confidence: 99%
“…15 After exacerbations of chronic obstructive pulmonary disease, readmission is more common among patients eligible for both Medicare and Medicaid, a marker of lower socioeconomic status. 16 Available data on PCI readmission suggest correlations with race and insurance status, with black patients nearly twice as likely to experience hospital readmission. 17 In addition to patient characteristics, hospital characteristics appear to be correlated with readmission.…”
Section: Lessons From Other Readmission Metricsmentioning
confidence: 99%
“…[14][15][16] Recent studies have suggested that the addition of COPD to the diagnoses included in the calculation of readmission penalties will only further harm hospitals serving large numbers of low SES patients. [17,18] Given the increasing penalties levied on institutions serving socioeconomically disadvantaged populations, the evaluation of relevant predictor variables for readmission in high-risk patients within low SES population has become an important topic for investigation. The purpose of the current study was to examine risk factors associated with 0-30-(30), 31-60-(60), and 61-90-(90) day all-cause hospital readmission in an underserved, socioeconomically disadvantaged patient population.…”
Section: Introductionmentioning
confidence: 99%